2006
DOI: 10.1590/s0100-54052006000100016
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do meio de cultura e do regime de luz na esporulação de Cercospora zeae-maydis

Abstract: Algumas espécies fúngicas não esporulam satisfatoriamente em meio de cultura, a exemplo de Cercospora zeae-maydis, agente causal da cercosporiose do milho. A esporulação deste patógeno foi avaliada em sete meios de cultura agarizados (V8, suco de tomate temperado, água de coco, aveia, BDA, extrato de folha de milho e extrato de folha de milho + CaCO3) sob dois regimes luminosos (fotoperíodo de 12 horas e seqüencial - 6 dias claro/3 dias escuro). O ensaio foi conduzido em esquema fatorial 7 x 2, com os tratamen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 7 publications
0
4
0
6
Order By: Relevance
“…Sutton. In addition, Brunelli et al (2006) reported good sporulation results for Cercospora zeae-maydis cultured in V8 under sequential light. These authors also emphasized that V8 medium contains more complex carbohydrates that can induce sporulation in mitosporic fungi.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Sutton. In addition, Brunelli et al (2006) reported good sporulation results for Cercospora zeae-maydis cultured in V8 under sequential light. These authors also emphasized that V8 medium contains more complex carbohydrates that can induce sporulation in mitosporic fungi.…”
Section: Discussionmentioning
confidence: 96%
“…Abiotic factors, such as temperature, luminosity and composition of the culture medium, are capable of inducing or inhibiting the vegetative and reproductive development of the majority of fungi (Dhingra & Sinclair, 1995;Brunelli et al, 2006). On Magnaporthe grisea (Hebert) Barr, for example, the composition of the culture medium influences the cultural characteristics of fungal colonies and sporulation (Dias Neto et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Isolates stored in sterile deionized water at 4ºC were transferred to PDA medium (200 g L -1 of potato, 20 g L -1 of dextrose, and 14 g L -1 of agar) and incubated for seven days at 27 ± 2°C with 12 hrs of light and 12 hrs of darkness. After that, they were transferred to tomato juice medium (STT -200 mL of SuperBom ® tomato juice, 3 g of CaCO 3 , 14 g of agar, and 800 mL of sterile water) and incubated at 25 ± 2°C under 12 hrs of light and 12 hrs of darkness for 15 days (Brunelli et al, 2006). Inoculum was prepared transferring five medium plugs colonized with the pathogen to sterile 125 mL Erlenmeyer flasks containing 20 g of sterile sorghum seeds and 16 mL of water.…”
Section: Inoculum Preparationmentioning
confidence: 99%
“…Isso ocorreu devido, em grande parte, à dificuldade de cultivo e esporulação deste fungo em meio de cultura. Entretanto, recentes trabalhos de cultivo in vitro de C. zeae-maydis contribuíram para contornar essa dificuldade ao estabelecer o meio de cultura e determinar as condições de temperatura e umidade ideais para o seu crescimento e esporulação (RUPE; SIEGEL; HARTMAN, 1982;THORSON;MARTINSON, 1993;BHATIA;MUNKVOLD, 2002;BRUNELLI et al, 2006;PAUL;MUNKVOLD, 2005;ASEA et al, 2005).…”
Section: Melhoramento Genético Visando Resistência a Cercospora Zeae-unclassified